GLP-1 Agonists in Type 1 Diabetes Mellitus. (August 2016) - Janzen, Kristin M.; Steuber, Taylor D.; Nisly, Sarah A.
Objective: To review the use of GLP-1 agonists in patients with type 1 diabetes mellitus (T1DM).Data Sources: A search using the MEDLINE database, EMBASE, and Cochrane Database was performed through March 2016 using the search terms glucagon-like peptide 1 (GLP-1) agonists, incretin, liraglutide, exenatide, albiglutide, dulaglutide, type 1 diabetes mellitus .Study Selection and Data Extraction: All English-language trials that examined glycemic end points using GLP-1 agonists in humans with T1DM were included.Data Synthesis: A total of 9 clinical trials examining the use of GLP-1 agonists in T1DM were identified. On average, hemoglobin A1C (A1C) was lower than baseline, with a maximal lowering of 0.6%. This effect was not significant when tested against a control group, with a relative decrease in A1C of 0.1% to 0.2%. In all trials examined, reported hypoglycemia was low, demonstrating no difference when compared with insulin monotherapy. Weight loss was seen in all trials, with a maximum weight loss of 6.4 kg over 24 weeks. Gastrointestinal adverse effects are potentially limiting, with a significant number of patients in trials reporting nausea.Conclusion: The use of GLP-1 agonists should be considered in T1DM patients who are overweight or obese and not at glycemic goals despite aggressive insulin therapy; however, tolerability of these agents is a potential concern. Liraglutide has the strongest evidence for use and would be the agent of choice for use in overweight or obese adult patients with uncontrolled T1DM.